CHARACTERIZATION OF INTERFEROGRAMS BY COMPUTER PROCESSING OF THEIR ANALOG IMAGES - Тихонов, Є. О.; Давиденко, В. О.; Батан, С. М. (Science-based technologies, 2011)
The method of digital recording and characterization of laser interference pattern using a microscope with digital eyepiece and the original two-beam interferometer for numerical assessment of spatial and temporal coherence is considered. Numerical methods for appropriate processing of interference image are realized with computational algorithm  of OriginPro-80/85. The effectiveness of techniques demonstrated by several examples of coherence measurement for the case of continuous gas and diode lasers.